1997
DOI: 10.1073/pnas.94.24.13273
|View full text |Cite
|
Sign up to set email alerts
|

The synthesis of ATP by glycolytic enzymes in the postsynaptic density and the effect of endogenously generated nitric oxide

Abstract: following correction should be noted. Due to an editorial change at PNAS, the meaning of the last sentence on page 14046 was altered. The sentence originally read as follows: On the other hand, this structure does not reproduce the pharmacological properties of either P or Q channel exactly, as the ID 50 to sFTX and -Aga IVA for P-type channels is lower than for the ␣1A, ␣2␦, ␤Ib channels in HEK cells.Neurobiology. In the article "The synthesis of ATP by glycolytic enzymes in the postsynaptic density and the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
86
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(95 citation statements)
references
References 75 publications
8
86
1
Order By: Relevance
“…glyceraldehyde-3-phosphate dehydrogenase, triosephosphate isomerase, phosphoglycerate mutase-1, and fructose-bisphosphate aldolase A. This is in agreement with a previous study, which demonstrated by immunoelectron microscopy the presence of glyceraldehyde-3-phosphate dehydrogenase in the dendritic spine and PSD (80). It was postulated that these proteins provide immediate availability of glycolytic source of ATP to the synapse.…”
Section: Discussionsupporting
confidence: 81%
“…glyceraldehyde-3-phosphate dehydrogenase, triosephosphate isomerase, phosphoglycerate mutase-1, and fructose-bisphosphate aldolase A. This is in agreement with a previous study, which demonstrated by immunoelectron microscopy the presence of glyceraldehyde-3-phosphate dehydrogenase in the dendritic spine and PSD (80). It was postulated that these proteins provide immediate availability of glycolytic source of ATP to the synapse.…”
Section: Discussionsupporting
confidence: 81%
“…It has been suggested (Raffin et al, 1992;Rosenthal and Sick, 1992) that the plasma membrane Na ϩ /K ϩ -ATPase is preferentially fueled by ATP produced from glycolysis (although it is unclear why mitochondrially produced ATP cannot diffuse to plasma membrane Na ϩ pumps, and an increase in glycolytic rate via the Pasteur effect might explain why mitochondrial block has relatively little effect). Consistent with a metabolic compartmentation within cells in which glycolysis powers ion pumping, glycolytic enzymes have been detected in synaptic locations where energy use on ion pumping is high (Wu et al, 1997;Ikemoto et al, 2003). This could explain why fueling glycolysis with glucose while blocking mitochondria prevents an AD; glycolytic ATP might allow the Na ϩ /K ϩ -ATPase to function sufficiently to maintain transmembrane ion gradients.…”
Section: Metabolic Compartmentationmentioning
confidence: 60%
“…Taken together, these findings indicate that ND2, but not the entire complex I, is normally present within the PSD. Many enzymes in the PSD may be involved in regulating synaptic function (39), including glycolytic enzymes capable of generating ATP (40). However, without the remaining components of complex I, it is unlikely that ND2 functions catalytically in the PSD.…”
Section: Discussionmentioning
confidence: 99%